Manajemen Pengadaan Bahan Pustaka di SMP Negeri 2 Kabupaten Langkat - Amelia Putri; Siti Hazrah; Siti Aisyah (Universitas Muhammadiyah Enrekang, 2022)
The school library is a place where students and teachers visit as other sources of information and knowledge. One of the attractions of library visitors is the library’s library library library library material and varied collections. One function of the school library is as a tool for students to learn to be informed persons, that is, students who are able to identify their needs, learn to search for and find sources of information that meet their needs. This study is vital in the hope of finding needed information and making a quality library appropriate for its function and commission. The methods used in this study are illustrative descriptive qualities-types of writing made appropriate to field conditions and from interviews.